Dental fluorosis and associated factors among Colombian schoolchildren: A Mixed Methods Study - Gutiérrez-Quiceno, Bruno; Ortega-Burbano, Yeimy Tatiana; Salcedo-Muñoz, Angye Paola; Reis da Silva, Rafaela; Moreno-Drada, Johana Alejandra (Revista Facultad Nacional de Salud Pública, 2025)
Objective: To identify the prevalence and factors associated with dental fluorosis (DF) among schoolchildren and to understand parent/guardian perception and knowledge concerning this condition. Methods: In this mixed methods study, researchers conducted clinical examinations on schoolchildren, as well as surveys and semi-structured interviews with parents/guardians in Nariño, Colombia, during 2023. The researchers analyzed data using descriptive statistics and multivariate analysis (quantitative), with the dependent variable fluorosis measured using Dean’s Index. Data was categorized according to content analysis (qualitative). The analysis of narratives and triangulation of the findings followed principles of grounded theory. Results: Using Dean’s index, the adjusted model found that prevalence of fluorosis increased with age among individuals with “very mild” versus “mild” levels (aOR = 1.85; 95%CI = 1.24-2.75) or in men (aOR = 3.08; 95% CI = 1.06-8.90) and was lower in those individuals who lived in urban areas (aOR = 0.21 95%; CI = 0.06-0.71) or among subjects who had a dental checkup three or more times per year (aOR = 0.12; 95% CI = 0.02-0.83). Prevalence also increased with age in individuals with very mild versus moderate levels (aOR = 2.21; 95% CI = 1.10-4.42) or in those whose parents reported knowing about fluorosis (aOR = 35.58; 95% CI = 3.50-361.14) and was lower in individuals who consumed the most popular salt brand in the area (aOR = 0.41; 95% CI = 0.002-0.90). Ten individuals participated in the semi-structured interview; a lack of knowledge was observed, and participants perceived DF as a natural or teeth-strengthening process. Through triangulation, age was identified as a factor interacting with fluorosis. Conclusion: The findings of this study suggest that frequency of dental checkups, age, sex, place of residence, parent/guardian knowledge and perception, and diet were associated with presence of DF.